CORPUS-BASED ANALYSIS OF MENTAL HEALTH DISCOURSE USING VOYANT TOOLS IN A JOURNAL ARTICLE - Arnelita Diva safira; Nayla Zalfaa’ Sugiarto; Kesya Nyctagina; Naila Kartika Pratiwi; Balqis Nur Faizah; Resti Rahmaa Nurjannah Al-‘asyra; Dewi Puspitasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines discussions of mental health through a corpus-based approach using Voyant Tools. The analysis focuses on a selected journal article titled “From Mental Health Crisis to Existential Human Suffering: The Role of Self-Transcendence in Contemporary Mindfulness.” The purpose of this study is to identify frequently occurring words and explain how these words reflect discussions of mental health. Qualitative corpus-linguistic methods were applied to analyze word frequency and linguistic patterns. Voyant Tools was used to generate frequency data and identify recurring words in the text. This analysis focused on nine keywords, including self, mindfulness, transcendence, mental, Buddha, student, existential, health, and medical. This study shows that the word “self” appears most frequently, indicating a strong emphasis on individual experience and self-awareness. The presence of “mindfulness” and “transcendence” reflects psychological and spiritual aspects. The terms “mental,” “health,” and “medical” indicate a clinical perspective. The word “students” highlights the connection between mental health and the educational context. The results of this study indicate that discussions of mental health are shaped by individual, psychological, spiritual, and medical perspectives. Voyant Tools provides a systematic approach to identifying linguistic patterns and supports the process of in-depth understanding in academic texts. This study makes a significant contribution to the field of corpus linguistics by demonstrating how digital tools can assist in analyzing discussions of mental health.